THEORETICAL STUDY OF CONCERTED DIELS-ALDER REACTIONS BETWEEN DIMETHYL 1,2,4,5-TETRAZINE-3,6-DICARBOXYLATE AND DIENOPHILES - Shneine, Jewad Kadhum; Mahmood, Shaima Mohamad Ali; Shihab, Mehdi Salih (Al-Nahrain Journal of Science, 2009)
Computational study at different levels of quantum calculations (AM1, PM3 and ab initio (HF/3-21G)) where preformed on the inverse-demand synchronous concerted Diels-Alder reactions between dimethyl 1,2,4,5-tetrazine-3,6-dicarboxylate as a diene and a variety of dienophiles (ethylene, cyclopentadiene, 1-hexene, cyclohexene). All the molecular structures (reactants, transition states, intermediates and adducts) were optimized by AM1 method. The calculated energies and volumes showed that the cycloaddition systems followed a mechanism by formation an intermediate and proceed to eject N2 molecule and ended by 1,2-hydrogen shift adduct. The prediction of the reaction energies of modeling of the cycloaddition reactions under-study by semiempirical AM1 method showed a good agreement with the experimental data comparing with PM3 and HF/3-21G. whereas, the prediction of activation energies by (AM1, PM3 and ab initio (HF/3-21G)) showed overestimated values comparing with experimental data.